Self‐Healing Inside APbBr3 Halide Perovskite Crystals. Issue 10 (12th January 2018) - Ceratti, Davide Raffaele; Rakita, Yevgeny; Cremonesi, Llorenç; Tenne, Ron; Kalchenko, Vyacheslav; Elbaum, Michael; Oron, Dan; Potenza, Marco Alberto Carlo; Hodes, Gary; Cahen, David
Abstract: Self‐healing, where a modification in some parameter is reversed with time without any external intervention, is one of the particularly interesting properties of halide perovskites. While there are a number of studies showing such self‐healing in perovskites, they all are carried out on thin films, where the interface between the perovskite and another phase (including the ambient) is often a dominating and interfering factor in the process. Here, self‐healing in perovskite (methylammonium, formamidinium, and cesium lead bromide (MAPbBr3, FAPbBr3, and CsPbBr3 )) single crystals is reported, using two‐photon microscopy to create damage (photobleaching) ≈110 µm inside the crystals and to monitor the recovery of photoluminescence after the damage. Self‐healing occurs in all three perovskites with FAPbBr3 the fastest (≈1 h) and CsPbBr3 the slowest (tens of hours) to recover. This behavior, different from surface‐dominated stability trends, is typical of the bulk and is strongly dependent on the localization of degradation products not far from the site of the damage. The mechanism of self‐healing is discussed with the possible participation of polybromide species. It provides a closed chemical cycle and does not necessarily involve defect or ion migration phenomena that are often proposed to explain reversible phenomena in halide perovskites. Abstract : Direct proof of self‐healing inside lead bromide perovskite crystals is provided. Two‐photon excitation, from high‐intensity sub‐bandgap (800 nm) pulsed illumination, allows damage to and monitoring deep (>100 μm) inside bromide perovskite single crystals via photoluminescence. Complete or partial recovery of photodamage is observed in minutes to hours. A complete chemical mechanism involving ABr3 species is proposed to explain the phenomenon.